The Art of Business Leadership : Indian Eperiences - S. Balasubramanian (Response, 2007)
This extremely interesting book proposes a new look at the complex world and characteristics of Indian business leadership. It is based on the author′s personal interaction and painstaking research on some of India′s leading businessmen and businesswomen, who have been very successful in transforming the organizations and the people they lead, into vibrant and growing entities. Presenting a unique perception and vision of business leadership in India, the book explores this complex subject and its dynamics in today′s challenging global business environment.